Circadian photoperiod alters TREK‐1 channel function and expression in dorsal raphe serotonergic neurons via melatonin receptor 1 signaling. Issue 2 (12th December 2020) - Giannoni‐Guzmán, Manuel A.; Kamitakahara, Anna; Magalong, Valerie; Levitt, Pat; McMahon, Douglas G.
Abstract: Seasonal day length has been linked to the prevalence of mood disorders, and however, the mechanisms underlying this relationship remain unknown. Previous work in our laboratory has shown that developmental exposure to seasonal photoperiods has enduring effects on the activity of mouse dorsal raphe serotonergic neurons, their intrinsic electrical properties, as well as on depression and anxiety‐related behaviors. Here we focus on the possible ionic mechanisms that underlie the observed programming of the electrophysiological properties of serotonin neurons, focusing on the twin‐pore K + channels TREK‐1 and TASK‐1 that set resting membrane potential and regulate excitability. Pharmacological inhibition of TREK‐1 significantly increased spike frequency in Short and Equinox photoperiods, but did not further elevate the firing rate in slices from Long photoperiod mice, suggesting that TREK‐1 function is reduced in Long photoperiods. In contrast, inhibition of TASK‐1 resulted in increases in firing rates across all photoperiods, suggesting that it contributes to setting excitability, but is not regulated by photoperiod. We then quantified Kcnk2 mRNA levels specifically in dorsal raphe 5‐HT neurons using triple‐label RNAscope. We found that Long photoperiod significantly reduced levels of Kcnk2 in serotonin neurons co‐expressing Tph2, and Pet‐1 . Photoperiodic effects on the function and expression of TREK‐1 were blocked in melatonin 1 receptor knockout (MT‐1KO) mice, consistent with previous findings that MT‐1 signaling is necessary for photoperiodic programming of dorsal raphe 5‐HT neurons. Taken together these results indicate that photoperiodic regulation of TREK‐1 expression and function plays a key role in photoperiodic programming the excitability of dorsal raphe 5‐HT neurons.